Synchrophasor data-based inertia estimation for regional grids in interconnected power systems - Zhang, Yiping; Qi, Feng; He, Yangdong; Wang, Bo; Yang, Deyou (Frontiers in Energy Research, 2022)
The inertia level is a significant indicator that guides operators to integrate renewable power generation into the power system for safe operation. In this study, a method that can estimate the effective inertia of power grids located in different regions in the interconnected system is proposed by using the synchronous measurement data. Based on the equivalent swing equation formed as a second-order oscillator, the inertia is expressed as a ratio of the time-evolution solution of this equation. To avoid a meaningless ratio, the Hilbert transformation is leveraged to recast the inertia analytical expression, which is composed of the time-independent characteristic parameters of the oscillation signal. Furthermore, the signal identification technique is employed to extract the characteristic parameters from the synchronized measurements so that the proposed scheme can estimate the regional inertia by using only the outputs measured by the synchorphasor measurement units. A comparison of the simulation results and methods validate the effectiveness and robustness of the proposed method.